2008
DOI: 10.1177/0143831x07085138
|View full text |Cite
|
Sign up to set email alerts
|

Free-Riding in Australia

Abstract: Free-riding has long been a contentious issue in Australian industrial relations. This article gauges the nature and location of free-riding in Australian workplaces, drawing on the 2004 Australian Worker Representation and Participation Survey. Of the 39.2 percent of employees who could join a union in their workplace and who do not, 51.7 percent may be characterized as deliberately free-riding. A similar proportion of employees may be described as `passive beneficiaries', for whom the costs of membership are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…This can be explained by the low variance in this variable, as most young graduates had only recently commenced their current jobs in the previous 24 months. Haynes et al . (2008: 22) found that after controlling for other variables, those workers with tenures between two and 10 years were no more or less likely than newer workers to be freeriders.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This can be explained by the low variance in this variable, as most young graduates had only recently commenced their current jobs in the previous 24 months. Haynes et al . (2008: 22) found that after controlling for other variables, those workers with tenures between two and 10 years were no more or less likely than newer workers to be freeriders.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the limitations of the data source, the analysis does not include some variables that have been found to increase the likelihood of an individual joining a union, namely perceived union instrumentality (Charlwood, 2002; Haynes et al ., 2008), perceived union performance (Bryson, 2006), perceived management attitudes to unions (Bryson, 2006), employee needs (Bryson, 2006) and ideology (Charlwood, 2002).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations